Performance of apricot varieties/genotypes in north western Himalayan region of India - Kumar, Dinesh; Singh, DB; Srivastava, KK; Singh, SR; Zargar, KA (SAARC Journal of Agriculture, 2017)
A long term experiment (2010-11 to 2014-15) was performed to evaluate the morphological and qualitative traits of apricot varieties/genotypes under north western Himalayan region of India. There were ten varieties/genotypes (CITH-Apricot-01, CITH-Apricot-02, CITH-Apricot-03, Communis, Erani, Afghani, Balcota, CITH-Apricot-09, Chinese apricot, Tokpopa Nimu ) were evaluated under RCBD with three replications. The results of five year pooled data indicated that maximum average Trunk Cross Sectional Area (TCSA) (168.03 cm2) was recorded in the variety Communis. Maximum fruit weight (80.03 g) and yield (113.87 kg/tree) were recorded in CITH-Apricot-01. The productivity efficiency (1.21 kg cm-2 TCSA) was noted in CITH-Apricot-02. The fruit stone ratio 21.62 was recorded in Afghani variety. The highest TSS (25.070 Brix) was estimated in CITH-Apricot-09. Acidity was noticed maximum in the variety Chinese apricot. The total sugar and non reducing sugar were manifested maximum in the apricot genotype Tokpopa Nimu and reducing sugar (8.9%) was recorded in CITH-Apricot-09 under the north western Himalayan region of India. SAARC J. Agri., 14(2): 107-116 (2016)